Sentimen Komentar Netizen dalam Postingan Pelantikan Menteri ATR/BPN Pada Akun Instagram @agusyudhoyono - Pristika, Febie Juma; Rozi, Fakhrur (KOMUNIKA, 2024)
The freedom of communication afforded by social media provides significant benefits to netizens by allowing them to interact and communicate without geographical restrictions or physical distance. Social media becomes a public forum to channel opinions or sentiments through comments. The sentiment of netizen comments refers to the opinions, responses, feelings, or views expressed by social media users (netizens) towards a particular topic, event, or content. This study aims to analyze the sentiments of netizens in the post of the Inauguration of the Minister of Agrarian and Spatial Planning / Head of the National Defense Agency (ATR / BPN) of the Advanced Indonesia Cabinet in the remaining term of office for the 2019-2024 period on the @agusyudhoyono Instagram account. This research uses qualitative methods with collection techniques in the form of observation and documentation. This research uses netnography theory. Netnography research aims to gain a deep understanding of the signification hidden in posts or responses made by netizens, which are observed from the perspective of the researcher. The results of this study indicate that netizen sentiment in the post of the inauguration of the Minister of ATR / BPN on the @agusyudhoyono Instagram account is mostly in the form of positive sentiment. Netizens' comments are in the form of congratulations, hopes, and prayers for Agus Yudhoyono. While negative sentiment is in the form of comments that reflect netizen disappointment with Agus Yudhoyono because he is no longer in opposition to the Jokowi administration